STUDI PADA HIMPUNAN WANITA DISABILITAS INDONESIA (HWDI) TENTANG KEWAJIBAN ORANG TUA PENYANDANG DISABILITAS DALAM PENGASUHAN ANAK (Analisis Hukum Islam dan Hukum Positif) - Ahmad fiqqih Alfathoni; Mardiana Mardiana (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2025)
This research is based on the problem of parenting patterns of parents with disabilities in caring their children and the implementation of the obligations of parents with disabilities in caring their children according to Islamic law and positive law, where there is a lot of stigma towards parents with disabilities by the society regarding parents with disabilities being doubtful, to be able to care for and fulfill the obligations of caring their children well. The method used in this research is qualitative with a statutory approach (Statute Approach), a comparative approach (Comparative Approach) and a sociological approach (Sociological Approach). The informants in this research were 6 (six) and 3 (three) informants who were disability observer figures in NTB. Data collection techniques use interviews, observation and documentation.The results of the research show that, the parenting style applied by parents with disabilities is a democratic parenting style, obligations according to Islamic law are mostly fulfilled and some parents with disabilities are unable to fulfill them. The obligations of parents with disabilities in caring for children according to positive law, Law of the Republic of Indonesia No. 35 of 2014 concerning Child Protection, have been fulfilled properly, however there are several obligations that parents with disabilities cannot fulfill